If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(5+6x)=18x+15
We move all terms to the left:
3(5+6x)-(18x+15)=0
We add all the numbers together, and all the variables
3(6x+5)-(18x+15)=0
We multiply parentheses
18x-(18x+15)+15=0
We get rid of parentheses
18x-18x-15+15=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 2r–15=-9r+18 | | 8x-2=-9+7× | | −12(4n+2)=19 | | -11-(-26)=x/12 | | (2x+5)+(6x-18)=180 | | 52=4y-16 | | 1/7=14-2x | | 15(9x-1)-14=133x+15 | | 7x-(2x-10)=25 | | 75=5w+13 | | 4/3=4n | | 2x*(x-2)=7x^2-7x | | 15x-15=7×-13 | | 2x+4+60=90 | | 13=7+3r | | x-1/2=-1/2 | | -2x+12=3x-103 | | x+1.5−0.5x=4.5x+1.5-0.5x=4.5 | | 2+2s=14 | | 54=4y-16 | | 4(x^2+19x+70)=544 | | -18x^2+19x-5=0 | | n/2=3/5 | | =52−4y16 | | 9x+2=7x-24 | | 13=9r+8 | | 2x-1/3x=0 | | -9x^2-9x+28=0 | | -3d+21=6 | | 2(2x-2)=9x | | 12(x+7)=60 | | -5x(3x+4)+2=0 |